Decontamination of beef carcasses and subprimal cuts - Curtis L. Kastner; P.B. Kenney; R.E. Campbell; R.K. Prasai; L.E. Mease; L.R. Vogt; Donald H. Kropf; Daniel Y.C. Fung; C.M. Garcia Zepeda (Kansas Agricultural Experiment Station Research Reports, 1994)
Lactic acid sprays effectively reduce the microbial load on both carcasses and subprimal cuts. Lactic acid decontamination of subprimals appears to carry through to retail cuts during display. Because of recontamination during fabrication, treating subprimals may be more effective than treating carcasses. This information will allow us to identify the most critical control points at which to employ decontamination practices designed to reduce the incidence of pathogenic bacteria and extend shelf life.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Microbiology; Decontamination; Carcass; Subprimal